Further Explanation on the Excitation Mechanism of Stay Cable Vibration in Dry Conditions - Duy Thao Nguyen; Duy Hung Vo (Buildings, 2023)
The present article outlines a research investigation carried out in a wind tunnel setting aimed at augmenting comprehension of the excitation mechanism of stay cable vibration in arid conditions. A multitude of wind tunnel experiments were thoroughly scrutinized. The study commenced by conducting measurements of the stay cable vibration in conditions of steady flow. The flow angle was set at 45 degrees, and the inclination was set at 25 degrees. The wind velocities varied during the experiment. Additionally, an investigation into the flow field surrounding the stay cable’s was conducted in both vertical and horizontal directions. By utilizing two hot wire anemometers in the cable wake, an extensive database of flow field measurements was obtained. The experimental results revealed that the vibration characteristics of the stay cable under the arid conditions considered in this study aligned with findings reported in existing literature. Notably, a deeper comprehension of the excitation mechanism of a stay cable in a dry state was attained. This mechanism is closely associated with the inhibition of Karman vortices and the development of low-frequency vortices. At low wind speeds, Karman vortices predominated, resulting in small-amplitude vibrations. However, as the wind speed increased, the influence of Karman vortices diminished progressively, while the low-frequency vortices grew stronger. These low-frequency vortices exhibited high energy and a significant correlation with shedding along the stay cable, thereby inducing cable vibration in a dry environment.